Anti-NMDA receptor encephalitis presenting as fever with undetermined cause - Chih-Wei Liang; Tun-Chieh Chen (International Journal of Infectious Diseases, 2022)
Autoimmune encephalitis is a rare disease, which should be differentiated from aseptic encephalitis. Possessing anti-N-methyl-D-aspartate (NMDA) receptor autoantibody is the leading cause of autoimmune encephalitis. However, it may pose a diagnostic challenge to clinicians, especially to nonpsychiatric or non-neurologic specialist, resulting in a delayed initiation of treatment. Hence, we share the case of a patient with anti-NMDA receptor encephalitis who was hospitalized in the infectious diseases ward, presenting with acute febrile illness that preceded characteristic neuropsychiatric symptoms.